A study of knowledge, awareness, and acceptance of contraception among reproductive age women at tertiary care hospital, Ahmedabad - Bamniya, Jaishree; Patel, Devanshi; Singh, Pooja; Chakravarti, Nisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: India is projected to be the most populous country according to United Nations’ report; therefore, the knowledge and awareness of contraceptive methods is of utmost important for small family norms and to increase inter-pregnancy interval, so that we can achieve optimum maternal and child outcomes. This study was conducted to assess knowledge, awareness, and acceptance of contraceptive methods among reproductive-age women during Corona pandemic. Methods: A prospective observational questionnaire-based study involving 513 women belonging to the 15-49 years of age group were interviewed with consent. This was a knowledge, attitude and practice (KAP) study regarding socio-demographic profile, knowledge, awareness, and acceptance of the contraceptive method. Results: Statistical analysis of data was done by using chi-square and percentage. Out of 513 participants, 63 participants were not using any method of contraception. Barrier method is the most commonly preferred method of contraception. There was significant association of education of women and husband, occupation with usage of contraception (p<0.001, p=0.016 and p<0.001). During corona pandemic acceptance of tubal ligation had taken a hit. Conclusions: During corona pandemic barrier method and oral contraceptive pills were preferred methods. In comparison with pre-COVID era data, tubal ligation was least preferred method. Acceptance of IUCD and Injectable contraception remained same. Higher education level and better financial status had correlation with increased awareness and acceptance of contraceptive methods.